If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = 3x + 2y Solving 6x = 3x + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6x + -3x = 3x + -3x + 2y Combine like terms: 6x + -3x = 3x 3x = 3x + -3x + 2y Combine like terms: 3x + -3x = 0 3x = 0 + 2y 3x = 2y Divide each side by '3'. x = 0.6666666667y Simplifying x = 0.6666666667y
| -2(x+5)-12=3(10-x) | | (7x+9)=36 | | 5(log(x)+7)=11 | | y-959=24 | | 2g=f+3 | | z-12=25 | | 9x-33=180 | | -2x+6=4x-12 | | 3f=g-4 | | x^7-25x^3=0 | | -100=d+334 | | 7X-4=4X+47 | | 5(x+3)-2(3x+7)=18 | | 3/5x+7=5 | | 91x+16=1895 | | 2x-6=-1+2x | | 672=-8j+56 | | y=2(0.92) | | 15x-11=59 | | y-20=2y-60 | | 6j+18=96 | | 8x-9=65 | | 10x+3=97 | | 8p-7p-4=p-4 | | y-20=2x-60 | | 15=18t+(-3t) | | 6x^3-14x^2-16x= | | -9b-10=-10b-9 | | 15x-30=25.20 | | -9+r+3-8=-2+3r | | g=tr | | -24+33x=9 |